2001
DOI: 10.1002/1521-3951(200111)228:2<345::aid-pssb345>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dopants on Defect Formation in GaN

Abstract: Subject classification:68.37Lp; S7.14 Influence of p-dopants (Mg and Be) on the structure of GaN has been studied using Transmission Electron Microscopy (TEM). Bulk GaN:Mg and GaN:Be crystals grown by a high pressure and high temperature process and GaN:Mg grown by metal-organic chemical-vapor deposition (MOCVD) have been studied. Structural dependence on growth polarity was observed in the bulk crystals. Spontaneous ordering in bulk GaN:Mg on cplane (formation of Mg-rich planar defects with characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…We further speculate that these hexagons might be related to the presence of Mg, as found earlier in GaN:Mg samples [27,[31][32][33][34][35], although the Mg concentration is much lower (~4x10 16 cm --3 ) in Sample B compared to samples described in the above references (~1x10 19 cm --3 ). However, the non-uniform distribution of these hexagons may indicate that there are regions (in sub-micron size) with locally higher Mg in this sample that cannot be detected by SIMS.…”
Section: Cross-sectional and Plan-view Tem Studiessupporting
confidence: 72%
See 1 more Smart Citation
“…We further speculate that these hexagons might be related to the presence of Mg, as found earlier in GaN:Mg samples [27,[31][32][33][34][35], although the Mg concentration is much lower (~4x10 16 cm --3 ) in Sample B compared to samples described in the above references (~1x10 19 cm --3 ). However, the non-uniform distribution of these hexagons may indicate that there are regions (in sub-micron size) with locally higher Mg in this sample that cannot be detected by SIMS.…”
Section: Cross-sectional and Plan-view Tem Studiessupporting
confidence: 72%
“…Tilting of the plan-view samples confirm that these hexagonal features are inverted pyramids. The presence of such features would suggest either the formation of pinholes protruding through the sample surface [27][28][29][30] or pyramidal inversion domains similar to those formed in highly Mg doped GaN samples [27,[31][32][33][34][35]. Such pinholes were observed earlier in samples with a high impurity density, especially with oxygen [28], where pinholes were formed not only at dislocations but also in dislocation free areas.…”
Section: Cross-sectional and Plan-view Tem Studiesmentioning
confidence: 98%
“…GaN extended defects include threading dislocations, [6][7][8] stacking faults, 8 open-core dislocations, [8][9][10][11] inversion domain boundaries, 10,12 V-defects in InGaN quantum wells (QW), [13][14][15][16][17][18] and pyramid shaped inversion domains and voids in Mg-doped GaN. [19][20][21][22][23][24] Because GaN and sapphire (Al 2 O 3 ), epitaxial GaN's most common substrate, are poorly matched in lattice parameter and thermal expansion coefficient, as-grown films have a high density of defects. The most common defects are threading dislocations, with typical densities of $10 10 cm À2 for molecular beam epitaxy grown films 7 and $10 8 cm À2 for metal organic chemical vapor deposition (MOCVD) films grown on SiN x nanonetworks.…”
Section: Introductionmentioning
confidence: 99%
“…Pyramid defect growth terminates when there is a lack of Mg on the defect walls and lateral overgrowth along the ð0001Þ planes is fast. [19][20][21][22][23][24] Here, we report a GaN defect discovered using aberration-corrected scanning transmission electron microscopy (STEM). This defect consists of a hexagonal (0001) based pyramid void with f10 11g side facets and produces a dislocation along the [0001] growth direction, some of which are open core screw dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…These defects have been studied in the literature and different models were suggested to explain their nature, all of them comprise an enrichment of Mg in the boundary or inside the PDs. Hansen et al [1] stated that the PDs are antibixbyite (Mg 3 N 2 ) precipitates, whereas Liliental-Weber et al [2][3][4][5] observed cavities inside PDs and assert that in the PDs the boundaries are decorated by Mg and covered by GaN of reversed polarity. Vennéguès et al [6] studied Mg doped bulk GaN grown by high-pressure, high-temperature method exhibiting rather large PDs with basal plane diameters of ∼100 nm.…”
Section: Introductionmentioning
confidence: 99%